STRATEGI INDUSTRILISASI HUBUNGAN DENGAN SEKTOR LAIN PADA PEMBANGUNAN - Pratidina, Revalina Tristian; Rizki Himawan Saputra; Muhammad Yasin (Nirta Akuntabel : The Indonesian Journal Of Economic and Accounting, 2026)
As a primary engine of economic development, industrialization is pivotal for raising productivity, creating jobs, and adding value. This qualitative study, grounded in a literature review, seeks to analyze the role of industrial strategies in economic advancement, examine the sector's economic relationships, and identify implementation difficulties. The research underscores that industrialization fosters growth through enhanced production, labor absorption, and structural transformation. Its close ties with the agricultural, commercial, and service sectors create positive spillover effects that benefit the wider economy. Yet, industrialization faces significant obstacles related to infrastructure, human capital, innovation, investment, and the environment. An integrated and sustainable approach to industrialization is thus required to ensure equitable economic development.